A PROFILE OF STUDENTS’ SKILLS IN WRITING LITERARYRESPONSES:REASONS FOR APPLYING EXPLICIT TEACHING OF TEXT TYPESIN WRITING ABOUT LITERATURE (A CASE STUDY) - Fiftinova Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: This study aimed to examine students’ skills in writing literary responses through functional perspectives. It was conducted in a college level literature classroom, where one teacher and three students presenting a different level of achievement, were involved. Three methods of data collection were used: observation, documentation and interview. Data analysis were done by identifying the teaching and learning activities that facilitated the writing, by identifying the schematic structures and the linguistic features of the students’ texts, lastly by categorizing students’ perception of writing literary responses in their classes. The findings showed that the teaching and learning activities were to some extent successfully done by the lecturer. She had applied Building Knowledge of the Field (BKOF), modeling stage, independence writing, and skipped joint construction. Modeling stage, however, was not conducted well since the lecturer did not explain clearly the schematic structures and the linguistic features of literary response text. As a result, the students’ writings were not really successful in the way that it fails to develop context and background information, to present appropriate tense and connectives. Finally, data from interview indicatedthat the students were not really familiar with writing literary response text by recognizing its purpose, its schematic structures, and its linguistic features. Consequently, these results reveal that the teaching of content and its appropriate language use in this setting were still taugt implicitly which was contrary to the concept of teaching genre recommended by the scholars. Key words:writing skills, literary response, functional grammar